Optimal size experimental plots for the selection of genotypes of bean - Smiderle, Éder Cristian; Botelho, Flávia Barbosa Silva; Guilherme, Scheila Roberta; Arantes, Sayonara Andrade do Couto Moreno; Botelho, Rodrigo Teixeira de Carvalho; Arantes, Kelte Resende (Comunicata Scientiae, 2014)
The determination of plot size in breeding programs is of great importance for the experimentcan be conducted accurately. Thus, the objective of this study was to determine the optimumplot size for the bean crop. We evaluated four bean lines: BRS Pérola, BRS Valente, BRS Requinteand BRS Radiante in two crops (off-season and winter crop) in 2010 in Sinop-MT. The experimentswere conducted in a randomized block design with three replications and plots with three rowsof two meters. We used the method of high curvature to evaluate the optimal size of the plot. Thecharacter was rated the weight of grain produced per plant. The basic unit used as a basis forcalculation was 15 plants. It was observed that the optimal size of the plot, according to the methodof Maximum Curvature, did not exceed 3m2. The behavior of the coefficient of variation (CV) wasalmost constant for all cultivars in both seasons. There was a tendency to stabilize CV (%), from plotsof size of approximately 7.5 m2.